Analysis of psychosocial stress factors in patients with renal cancer. Issue 6 (June 2018) - Draeger, Désirée Louise; Sievert, Karl-Dietrich; Hakenberg, Oliver W.
Background: The experience of stress in patients with cancer through helplessness and the suppression of emotions correlates with unfavorable disease prognosis. Significant distress can reduce survival probability as well as subjectively perceived poor quality of life. Currently, there are few data on psychological stress in patients with renal cancer and most studies focus on survival time. The aim of the study was to evaluate the psychosocial stress of patients with renal cancer with screening questionnaires for an inpatient psychosocial treatment program. Methods: Patients undergoing inpatient surgical or medical treatment for renal cancer were prospectively assessed for psychosocial stress with two standardized stress screening questionnaires used for the identification of the need for psychosocial care [NCCN Distress Thermometer (NCCN-DT), Hornheider Screening Instrument (HSI)]. Results: Seventy-four patients with a mean age of 65 years were assessed. The average NCCN-DT score was 4.8 (scale of 0–10) and did not correlate with tumor stage, sex or prognosis. According to the DT results, 27% of patients were in need of psychosocial care which was significantly higher than the self-reported need. The main stressors were anxiety (32%), pain (27%), nervousness (26%), sadness, worry and sleeping difficulties (20%). Conclusions: There is a significant number of patients with renal cancer with increased psychological distress and a consecutive need for psychosocial care. This is underreported and largely unrecognized by patients as well as physicians and nurses. Easy-to-use assessment tools can be very helpful in identifying patients in need and this information can be used to implement psychological support and thus improve patient care.